2003
DOI: 10.1002/jbt.10100
|View full text |Cite
|
Sign up to set email alerts
|

Garlic attenuates chrysotile‐mediated pulmonary toxicity in rats by altering the phase I and phase II drug metabolizing enzyme system

Abstract: Asbestos and its carcinogenic properties have been extensively documented. Asbestos exposure induces diverse cellular events associated with lung injury. Previously, we have shown that treatment with chrysotile shows significant alteration in phase I and phase II drug metabolizing enzyme system. In this study we have examined some potential mechanisms by which garlic treatment attenuates chrysotile-mediated pulmonary toxicity in rat. Female Wistar rats received an intratracheal instillation of 5 mg chrysotile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 51 publications
(40 reference statements)
1
10
0
1
Order By: Relevance
“…It is difficult to discuss the results of the influence of garlic extracts, because the preparations (a), amounts (b) and applications (c) were different in each report: (a) homogenization in water of 100 mg/kg/day (Baluchnejadmojarad and Roghani, 2003); (b) 500 mg/kg (Ameen et al, 2003); 250 mg/ kg (Arivazhagan et al, 2004); 2.0 -4.0% dry powder or curcumin (0.2%)/capsaicin (0.015%)/garlic (2.0% dry powder) added to the diets (Kempaiah and Srinivasan, 2004;PedrazaChaverrí et al, 2000;Yeh et al, 2005); (c) intragastric intubation; administration in saline; injection of 1.2 mL/kg body weight/24 h/6 days subcutaneously and intraperitoneally; dried powders as supplementation to diets (Arivazhagan et al, 2004;El-Demerdash et al, 2005;Maldonado et al, 2003;Shin and Kim, 2004).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is difficult to discuss the results of the influence of garlic extracts, because the preparations (a), amounts (b) and applications (c) were different in each report: (a) homogenization in water of 100 mg/kg/day (Baluchnejadmojarad and Roghani, 2003); (b) 500 mg/kg (Ameen et al, 2003); 250 mg/ kg (Arivazhagan et al, 2004); 2.0 -4.0% dry powder or curcumin (0.2%)/capsaicin (0.015%)/garlic (2.0% dry powder) added to the diets (Kempaiah and Srinivasan, 2004;PedrazaChaverrí et al, 2000;Yeh et al, 2005); (c) intragastric intubation; administration in saline; injection of 1.2 mL/kg body weight/24 h/6 days subcutaneously and intraperitoneally; dried powders as supplementation to diets (Arivazhagan et al, 2004;El-Demerdash et al, 2005;Maldonado et al, 2003;Shin and Kim, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…Garlic was studied in different forms of extracts: aqueous, ethanol, dried powders (Shin and Kim, 2004;Tsao et al, 2003;Ameen et al, 2003). It was shown that aqueous garlic extract alleviates ischaemia -reperfusion-induced oxidative hepatic injury in rats (Sener et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Catalytic antioxidants have been shown to have protective effects against silicainduced injury, including the porphyrin MnTBAP (123) and the nitroxide TEMPO (205). Thiol-based antioxidants also have protective effects in the silica-induced injuries, including NAC and GSH (12), as well as garlic extracts that are rich in thiol-containing compounds (6). The lazaroid compounds U-75412E and U-74389G are also effective against silica-induced injury (7,85).…”
Section: Fibrogenic Environmental Agents and Oxidative Stressmentioning
confidence: 99%
“…Garlic has been shown to potentially modulate the activity of transferases and cytochrome P450 isozymes, both in vitro and in vivo (8). If these effects occur in patients treated for malignancy, then garlic has the potential to impair the metabolism of many clinically important agents, including the CYP3A4 substrate drug docetaxel ( Fig.…”
Section: Passage Of the Dietary Supplement Health And Education Actmentioning
confidence: 99%